Alkaloids of Zephyranthes citrina (Amaryllidaceae) and their implication to Alzheimer's disease: Isolation, structural elucidation and biological activity - Kohelová, Eliška; Maříková, Jana; Korábečný, Jan; Hulcová, Daniela; Kučera, Tomáš; Jun, Daniel; Chlebek, Jakub; Jenčo, Jaroslav; Šafratová, Marcela; Hrabinová, Martina; Ritomská, Aneta; Malaník, Milan; et al. (Bioorganic chemistry, 2021)
Twenty known Amaryllidaceae alkaloids of various structural types, and one undescribed alkaloid of narcikachnine-type, named narcieliine (3), have been isolated from fresh bulbs of Zephyranthes citrina. The chemical structures of the isolated alkaloids were elucidated by a combination of MS, HRMS, 1D and 2D NMR, and CD spectroscopic techniques, and by comparison with literature data. The absolute configuration of narcieliine (3) has also been determined. Compounds isolated in a sufficient quantity were evaluated for their in vitro acetylcholinesterase (AChE; E.C. 3.1.1.7), butyrylcholinesterase (BuChE; E.C. 3.1.1.8), and prolyl oligopeptidase (POP; E.C. 3.4.21.26) inhibition activities. Significant human AChE/BuChE (hAChE/hBuChE) inhibitory activity was demonstrated by the newly described alkaloid narcieliine (3), with IC50 values of 18.7 ± 2.3 µM and 1.34 ± 0.31 µM, respectively. This compound is also predicted to cross the blood-brain barrier (BBB) through passive diffusion. The in vitro data were further supported by in silico studies of 3 in the active site of hAChE/hBuChE.
Keywords: molekulární konformace; Molecular Conformation; Catalytic Domain; Alkaloids; Humans; Narcieliine; alkaloidy; simulace molekulového dockingu; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; hematoencefalická bariéra; Blood-Brain Barrier; Molecular Docking Simulation; vazebná místa; lidé; Alzheimer Disease; magnetická rezonanční spektroskopie; Alzheimerova nemoc; Amaryllidaceae; Binding Sites; Docking studies; cholinesterasové inhibitory; Zephyranthes citrina; Kinetics; butyrylcholinesterasa; katalytická doména; Acetylcholinesterase; Alzheimer's disease; Magnetic Resonance Spectroscopy; Cholinesterase Inhibitors; Butyrylcholinesterase; acetylcholinesterasa; kinetika